Adhesive properties of Vibrio cholerae: adhesion to isolated rabbit brush border membranes and hemagglutinating activity. - Jones, G W (1976)
Adhesion of vibrios to the small intestine may occur (i) by association of the bacteria with secreted mucus gel or (ii) by adherence of the bacteria to the surface of epithelial cells. In the present study, vibrios readily adhered to isolated brush border membranes obtained from rabbit intestinal epithelial cells. Adhesion was temperature dependent and required the presence of divalent cations such as calcium. The agglutination of human O erythrocytes by Vibrio cholerae was observed also, and the hemagglutination test appeared to detect the same mechanism that was involved in the adhesion of vibrios to brush borders. When the bacteria were grown in broth they were adhesive and hemagglutinating, but vibrios grown on agar plates or suspended in buffer for 15 min at 37 C lacked these abilities, even though they retained undiminished motility. These two model systems differed, however, in that strontium promoted only adhesion to brush borders. The significance of this difference remains to be determined. Vibrios were observed to penetrate intestinal mucus gel and occasionally to become entrapped in it. However, there was no evidence that vibrios attached to mucus gel.